What Does Melville See on the Ocean? - Stipe Grgas ([sic])
The article begins with a brief discussion of what the author judges to be an overproduction of publications in literary studies. He offers an explanation of this development and contends that the causes are endemic to the humanities. Two causes of this overproduction are particularly pertinent for his reading of Melville: firstly, the constant change of interpretative paradigms and, secondly, the striving of the humanities to reflect upon the contemporary moment. The departure point of the reading is the spatial turn and the author's contention that this geographical knowledge has failed to address the sea. Elaborating on this contention, the author foregrounds the need for a maritime criticism and proceeds to read Moby Dick by excavating the manner in which Melville represents and thinks of the sea. On the basis of this evidence, the author argues that in Moby Dick, Melville offers a meontological thinking of the sea. Consequentially, the author argues that this meontology has a bearing on the present economic crisis and that it can be used in understanding the latest mutation of money. In the conclusion, the author claims that literary studies can make an important contribution to efforts to cope with the challenges of the present moment.